A phygital approach to cultural heritage: augmented reality at Regaleira - Andrade, José Gabriel (2021)
In the last two decades, contemporary society has been conceptualized and discussed around the assumption that digital technologies are its most defining feature. Jean Baudrillard's take on the Fable of Borges suggests a replacement of the physical world by a virtual experiencing life, setting the tone for a pessimistic and somewhat fearful attitude towards technological development. On the verge of the dissemination of disruptive innovations that can be described under the "umbrella" of Internet of Things (IoT), we observe not a replacement, but a deep and complex intertwining of online and offline experiences, sketching the contours of what can become a phygital society. This alternative conceptualization of our contemporary society, combined with the possibilities of technological development, provides new opportunities for the expression and experiencing of culture, and also for the creative industries. In our research, we explore the impact of one augmented reality (AR) app designed for one of the landmarks of Portuguese cultural heritage, Quinta da Regaleira. We explore this unique case study using qualitative data collection techniques, aiming to discuss the positive and negative outcomes of this innovation, both for the dynamization of cultural heritage, and for visitors. The article provides useful information for heritage spaces that wish to follow this path. It describes the main steps to be taken in the production of content and provides examples of the narrative model that helps people to visit the space and obtain information, knowing stories relevant to the past and present of the cultural heritage. The objective is to clarify, finally, due to the research developed in the Quinta da Regaleira case study, what kind of stories and experiences can be narrated, the strengths of this application, its limitations, and paths for future investigations.